The effect of sodium silicate and its solution on the properties of refractory complex binder/Natrio silikato kiekio ir jo tirpalo tankio įtaka kompleksinio kaitrai atsparaus rišiklio savybėms - Antonovič, Valentin; Goberis, Stasys; Mačiulaitis, Romualdas (Journal of Civil Engineering and Management, 1999)
In order to improve thermal and mechanical characteristics of a traditional binder with liquid glass a complex binder consisting of liquid glass, its hardener and alumina cement (“Gorkal 70” containing not less than 70 per cent of AI2O3) was tested. Sodium silicate and its solution effect on physical and mechanical properties of a new refractory complex binder (Table 1, Fig 2) were investigated. The results obtained show that compressive strength of binding compound with high quantity of sodium silicate (N3) is the lowest after it had been cured, dried and fired at 300–600°C (Fig 3). It was also found that the strength of a complex binder with small quantity of sodium silicate (N1) in the temperature range of 20–600°C is 2–3 times as high as that of a traditional binder with dispersed fire-clay. The study in the formation of the structure of a complex binders dilatometric tests have also been made. After initial heating at 80–500°C the compositions contracted (Fig 4) due to dehidratation. At the temperature range of 580–750°C the contraction of compositions continue due to reactions at the solid phase. The hypothesis of the hardening mechanism in the complex binder was proposed. Liquid glass tends to restrain the hydration of the alumina cement though hardeners and sodium silicate interaction result in the intense formation of sodium calcium hydrosilicates. Therefore, a complex binder contains less sodium silicate than a traditional one while being used at higher temperature. First Published Online: 26 Jul 2012